Revisiting dependences of the drag coefficient at the sea surface on wind speed and sea state. (16th December 2020) - Lin, Shangfei; Sheng, Jinyu
Abstract: Accurate representation of wind stress is important for modelling and predictions of marine environmental conditions. The effect of sea state on wind stress is usually parameterized by relating the equivalent sea surface roughness to the wave age or wave steepness. In this study, a new parameterization is presented for the dependences of sea surface roughness on the wind speed and sea state based on observations. Analyses of observations demonstrate that the sea surface roughness is correlated with the wave age stronger than the wave steepness. As a result, the wave-dependent sea surface roughness is parameterized in terms of the wave age in the new parameterization. The new parameterization features that the sea surface roughness has different dependences on the wave age under wind-sea-dominated, mixed and swell-dominated sea states. Younger waves have larger values of the drag coefficient under wind-sea-dominated and mixed sea states but older waves have larger values under swell-dominated sea states. The drag coefficient predicted by the new parameterization is enhanced at low winds and levels off at high winds. The applicability of the new parameterization is investigated using a nested-grid wave model for the northwest Atlantic based on WAVEWATCH III. The wave model results during a winter storm in March 2014 are compared with the available measurements from buoys and satellite altimeters over the study region. Our results demonstrate that the new parameterization reduces deficiencies of three existing parameterizations of underestimating significant wave heights (SWHs) at low winds (or old waves) and overestimating SWHs at moderate and high winds (or young waves). Overall, the new parameterization performs the best in predicting SWHs during the winter storm in comparison with the existing schemes. Highlights: Analyses of the dependences of the drag coefficient on the wind speed and sea state. Development of a new wave-dependent parameterization for the drag coefficient. Investigation of the applicability of different parameterizations for the drag coefficient in wind wave simulations.